Dithiol Oxidant and Disulfide Reductant Dynamically Regulate the Phosphorylation of Light-Harvesting Complex II Proteins in Thylakoid Membranes - Martinsuo, Päivi (Plant Physiol, 2003)
Light-induced phosphorylation of light-harvesting chlorophyll a/b complex II (LHCII) proteins in plant thylakoid membranes requires an activation of the LHCII kinase via binding of plastoquinol to cytochrome b(6)f complex. However, a gradual down-regulation of LHCII protein phosphorylation occurs in higher plant leaves in vivo with increasing light intensity. This inhibition is likely to be mediated by increasing concentration of thiol reductants in the chloroplast. Here, we have determined the components involved in thiol redox regulation of the LHCII kinase by studying the restoration of LHCII protein phosphorylation in thylakoid membranes isolated from high-light-illuminated leaves of pumpkin (Cucurbita pepo), spinach (Spinacia oleracea), and Arabidopsis. We demonstrate an experimental separation of two dynamic activities associated with isolated thylakoid membranes and involved in thiol regulation of the LHCII kinase. First, a thioredoxin-like compound, responsible for inhibition of the LHCII kinase, became tightly associated and/or activated within thylakoid membranes upon illumination of leaves at high light intensities. This reducing activity was completely missing from membranes isolated from leaves with active LHCII protein phosphorylation, such as dark-treated and low-light-illuminated leaves. Second, hydrogen peroxide was shown to serve as an oxidant that restored the catalytic activity of the LHCII kinase in thylakoids isolated from leaves with inhibited LHCII kinase. We propose a dynamic mechanism by which counteracting oxidizing and reducing activities exert a stimulatory and inhibitory effect, respectively, on the phosphorylation of LHCII proteins in vivo via a novel membrane-bound thiol component, which itself is controlled by the thiol redox potential in chloroplast stroma.